Petroleum hydrocarbon (PHC) uptake in plants: A literature review - Hunt, Lillian J.; Duca, Daiana; Dan, Tereza; Knopper, Loren D. (Environmental pollution (1987), 2019)
Crude oil and its constituents can have adverse effects on ecological and human health when released into the environment. The Canadian Council of Ministers of the Environment (CCME) has developed remedial guidelines and a risk assessment framework for both ecological and human exposure to PHC. One of the assumptions used in the derivation of these guidelines is that plants are unable to take up PHC from contaminated soil and therefore subsequent exposure at higher trophic levels is not a concern. However, various studies suggest that plants are indeed able to take up PHC into their tissues. Consumption of plants is a potential exposure pathway in both ecological (e.g., herbivorous and omnivorous birds, and mammals) and human health risk assessments. If plants can uptake PHC, then the current approach for risk assessment of PHC may underestimate exposures to ecological and human receptors. The present review aims to assess whether or not plants are capable of PHC uptake and accumulation. Twenty-one articles were deemed relevant to the study objective and form the basis of this review. Of the 21 primary research articles, 19 reported detectable PHC and/or its constituents in plant tissues. All but five of the 21 articles were published after the publication of the CCME Canada-Wide Standards. Overall, the present literature review provides some evidence of uptake of PHC and its constituents into plant tissues. Various plant species, including some edible plants, were shown to take up PHC from contaminated soil and aqueous media in both laboratory and field studies. Based on the findings of this review, it is recommended that the soil-plant-wildlife/human pathway should be considered in risk assessments to avoid underestimating exposure and subsequent toxicological risks to humans and wildlife. [Display omitted] •Consumption of plants is a potential exposure pathway in health risk assessments.•Common pardigm is that plants are unable to take up PHC from soil.•Plants are indeed able to uptake PHC in their tissues.•As such, the current approach for risk assessment of PHC may underestimate exposure.•The soil-plant-wildlife/human pathway should be considered in risk assessments of PHC exposure. The findings of this review indicate that the soil-plant-wildlife/human exposure pathway may be complete and as such, risk assessors may want to consider more fully this pathway in human and ecological risk assessments.